2021
DOI: 10.3390/ijerph182413417
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Falls from Height Variables in Occupational Accidents

Abstract: Fall-from-height accidents are linked to severe and fatal consequences for impacted workers. A better understanding of the related variables is necessary to improve worker safety. This study analyzed all fall-from-height occupational accidents recorded in Spain from 2009 to 2019, selected significant variables, and evaluated the influence concerning the seriousness of the falls from height. Based on a total of 290,583 fall-from-height accidents, the study shows that a male inexperienced worker in a small compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…This may be explained by the younger age and lower prevalence of comorbidities observed in border falls. Other studies have observed a significant correlation between fall height and number and extent of injuries 11–13. Richter et al similarly examined patients who fell from 24 ft between patients who fell accidentally, and those who committed suicide, yet conversely from our study, found no differences between accidental versus intentional injuries 11.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…This may be explained by the younger age and lower prevalence of comorbidities observed in border falls. Other studies have observed a significant correlation between fall height and number and extent of injuries 11–13. Richter et al similarly examined patients who fell from 24 ft between patients who fell accidentally, and those who committed suicide, yet conversely from our study, found no differences between accidental versus intentional injuries 11.…”
Section: Discussionsupporting
confidence: 49%
“…The three patients who died were much older than average, at 56 (46–50) years, all had an ISS of at least 33, and an admission GCS between 3 and 8. Other studies on falls from height typically had worse morbidity and mortality than this population, due to a higher age range of intentional falls 10–13…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Falls from height are a leading cause of serious occupational injury and fatality globally 1–7. In 2013 alone, falls from height accounted for 36.9% of total occupational fatalities in the USA, 31% in the UK and 12% in Australia 1.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars mainly analyze the influencing factors of construction workers’ unsafe behavior from following four aspects: human, material, management, and environment. For example, psychological capital ( Eid et al, 2012 ), physiology ( Yang et al, 2021 ), safety awareness and attitude ( Mohajeri et al, 2021 ; Liang et al, 2022 ), and work experience ( Alizadeh et al, 2015 ; Rey-Merchán et al, 2021 ) are human factors; personal protective equipment ( Amiri et al, 2014 ) and construction equipment ( Castillo-Rosa et al, 2017 ) are material factors; safety promotion policy ( Man et al, 2021 ), safety training ( Man et al, 2021 ), safety atmosphere ( Liao et al, 2014 ), safety supervision ( Fang et al, 2015 ), safety management, and safety culture ( Wang et al, 2016 ; Asilian-Mahabadi et al, 2018 ) are management factors; and working environment ( Harsini et al, 2021 ) and social environment ( Aven and Renn, 2009 ; Ma et al, 2021 ) are environmental factors. However, these studies only focus on the explicit analysis of the influencing factors of construction workers’ unsafe behavior, and few studies have focused on the implicit correlation analysis between the influencing factors.…”
Section: Introductionmentioning
confidence: 99%